Intermediate osteotomy: the vital pivot, in the wide nose - Munjal, Manish; Munjal, Shubham; Arora, Vineeta; Sharma, Salony; Talwar, Shivam; Chawla, Deeksha; Kaur, Hardeep; Grewal, Mehtab; Gupta, Vasu; Bharadwaj, Iti; Sidhu, Kanwarpreet; Joshi, Tanvi (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Deviations and deformities of the bony nasal skeleton are amenable to osteotomies in the longitudinal, transverse and the oblique planes. These interventions undertaken either intranasal or percutaneous, translocate the osteo-cartilaginous nasal segments as a single entity. The intermediate osteotomy is usually resorted to, in three situations, namely; a very broad nose with a good nasal height, a deviated nose with a lateral wall longer than the opposite and where required to straighten an excessively convex nasal bone. A lady with quite a broad nose was subjected to bilateral osteotomies of the ‘intermediate’ type, to achieve aesthetic social acceptability.